الغسيل الكُلوي وأثره في انتقاض الوضوء - محمد ابراهيم احمد (مجلة كلية العلوم الأسلامية)
There are numerous emerging issues in Islamic jurisprudence, as the scriptural texts are finite, while new issues continue to arise indefinitely. It is essential to research these new matters and relate or compare them to the issues discussed by early jurists. Muslims need to understand the legal rulings on new issues to ensure the correctness of their acts of worship. The nullification of wudu (ablution) is a crucial legal matter, as it is foundational to the performance of one of the greatest pillars of Islam—prayer. Therefore, Muslims must be aware of the rulings on new issues related to wudu, whether they nullify it or not. Researching these matters helps students of knowledge develop a firm understanding of jurisprudential rulings. Thus, this study examines the issue of dialysis and its impact on the nullification of wudu.